Perancangan Aplikasi Sistem Informasi Pencatatan Perjalan Dinas Berbasis Mobile pada PT. Perkebunan Nusantara IV Medan - Alda, Muhamad; Kartika, Dewi; Syafriani, Dini; Amanda, Retno Tri (MODELING: Jurnal Program Studi PGMI, 2023)
PT Perkebunan Nusantara IV Medan currently does not have a system that can assist in the process of recording business trips. In general, management of letters, especially Business Travel Orders or SPPD, is very important for every government agency or company. In addition to the SPPD, the official travel document that employees need is an accountability sheet that contains details of travel expenses. In making the SPPD, there are currently many deficiencies that must be faced, such as the occurrence of typing errors in inputting data so that the creation of the SPPD is carried out repeatedly, and also the search for proposed employee data, and the assigning employee in making the SPPD has not been done automatically so it requires longer time. As well as calculating the cost of official travel is also still done manually by the HR executive staff. To overcome this problem, a better system is needed so that the recording of official travel at PT Perkebunan Nusantara IV Medan becomes more effective and efficient. Therefore, a Mobile-based official travel recording application was created to manage business trips at PT Perkebunan Nusantara IV Medan. Making this application using the waterfall software development method. The stages of the waterfall model start from planning, analysis, design, implementation and maintenance. By using a computerized system, the results of the implementation show that this application is easy to use and recording official travel at the company is faster. Making an Official Travel Order becomes easier, can save time, and minimizes errors that may occur. Facilitate the data search process, because the SPPD that has been created is stored in the database.